HUBUNGAN PENERAPAN PIJAT PERINEUM UNTUK MENGURANGI RUPTUR PERINEUM SAAT PERSALINAN DI KLINIK PRATAMA RATNA KOMALA TAHUN 2020 - Siregar, Renince (STIKes Medistra Indonesia, 2021)
The incidence of perineal lacerations needs to be prevented, one of which is perineal massage. The perineum is the area of ​​skin between the vaginal canal and the anus (anus) which can be torn during childbirth (Herdiana, 2014). Perineal massage is one of the oldest and surest ways to promote healthy blood flow, elasticity, and relaxation of the pelvic floor muscles (Hadiningsih 2014:155). This study aims to determine